The supply chain of AIBL: how can AIBL maintain a sustainable supply chain? - Sinan, Saleh Md. Abu (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.